Implementation of Science Environment Technology and Society Approach on Learning Critical Thinking Skills - Denny Rachmadi (International Conference on Science, Education, and Technology, 2023)
Research on the implementation of the science environment technology ad society approach to learning critical thinking skills is qualitative research using a non-equivalent control group design which is included in the quasi-experimental design group. This study aims to determine the effect of the implementation of science environment technology and society on critical thinking skills in students. This research was conducted at SMAN 1 Purwodadi. The participants in this study are students of science class 2 (IPA 2) as an experimental class that implements science environment technology and society in learning while science class 3 (IPA 3) as a control class whose learning does not use the implementation of science environment technology and society. The results of the study obtained the percentage of achievement of critical thinking skills of experimental class students was better than the critical thinking skills of control class students. Thus, it can be concluded that there is an influence of the implementation of the science, environment, technology and society approach on learning on students' critical thinking skills.